Applications of Infrared and Raman Microspectroscopy of Cells and Tissue in Medical Diagnostics: Present Status and Future Promises. Issue 5 (11th July 2012) - Diem Diem, Max Max; Miljković Miljković, Miloš Miloš; Bird Bird, Benjamin Benjamin; Chernenko Chernenko, Tatyana Tatyana; Schubert Schubert, Jen Jen; Marcsisin Marcsisin, Ellen Ellen; Mazur Mazur, Antonella Antonella; Kingston Kingston, Erin Erin; Zuser Zuser, Evgenia Evgenia; Papamarkakis Papamarkakis, Kostas Kostas; Laver Laver, Nora Nora
Abstract : This paper summarizes the progress achieved over the past fifteen years in applying vibrational (Raman and IR) spectroscopy to problems of medical diagnostics and cellular biology. During this time, a number of research groups have verified the enormous information content of vibrational spectra; in fact, genomic, proteomic, and metabolomic information can be deduced by decoding the observed vibrational spectra. This decoding process is aided enormously by the availability of high-power computer workstations and advanced algorithms for data analysis. Furthermore, commercial instrumentation for the fast collection of both Raman and infrared microspectral data has rendered practical the collection of images based solely on spectral data. The progress in the field has been manifested by a steady increase in the number and quality of publications submitted by established and new research groups in vibrational biological and biomedical arenas.